Bundled innovations for women’s empowerment and resilience - Jain, Harsha; Gartaula, Hom Nath; Shivhare, Riche; Nayak, Prakash Kumar; Chadha, Deepali; Johri, Yash; Mukhopadhyay, Prama; Goel, Kritika; Dullo, Anandita; Puskur, Ranjitha (CGIAR Initiative on Gender Equality, 2024)
Climate change is exacerbating uncertainty and risks for farmers and other food systems actors in unprecedented ways. Women and marginalized farmers face higher vulnerabilities as they often encounter additional barriers in the form of constraining social and gender norms.